2019
DOI: 10.1111/aogs.13609
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of 49 933 women with surgically verified endometriosis: Increased incidence of breast cancer below the age of 40

Abstract: Introduction: The association between endometriosis and breast cancer is unclear. We assessed the risk of breast cancer in women with surgically verified endometriosis, with special focus on the age at cancer diagnosis, time from endometriosis diagnosis and breast cancer histology. Material and Methods: All women with first endometriosis associated diagnoses occurring concomitantly with relevant surgical codes during 1987-2012 were retrieved from the Finnish Hospital Discharge Register in Finland. Breast cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Data on the association between endometriosis and breast cancer are less consistent due to different reasons that have been reviewed elsewhere [ 9 , 10 ]. On the one hand, some studies provide evidence that women with endometriosis are more vulnerable to develop breast cancer, although they show contradicting results with regard to the age when this increased susceptibility is observed [ 11 , 12 ]. On the other hand, another group of studies are supportive of a negative association between endometriosis and breast cancer, the former possibly conferring protection from the latter [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the association between endometriosis and breast cancer are less consistent due to different reasons that have been reviewed elsewhere [ 9 , 10 ]. On the one hand, some studies provide evidence that women with endometriosis are more vulnerable to develop breast cancer, although they show contradicting results with regard to the age when this increased susceptibility is observed [ 11 , 12 ]. On the other hand, another group of studies are supportive of a negative association between endometriosis and breast cancer, the former possibly conferring protection from the latter [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the majority of the studies supported an association between the two, issues regarding the association between endometriosis and BC risk are still inconclusive 46 , 47 . A study reported that the overall risk of BC in women with surgically verified endometriosis was similar to that in the general population 48 . We do not know the exact mechanisms involved in an inverse association between endometriosis and BC, but Matta et al suggested that higher DNA repair capacity (DRC) in women with endometriosis and/or hormonal treatments for endometriosis may provide specific protective effects for BC 49 .…”
Section: Discussionmentioning
confidence: 90%
“…The standardized incidence of in situ breast cancer increased in the 40-to 59-year-old age group; however, patients with EMS aged 40 years or older might undergo breast imaging more frequently than the general population, which could potentially increase the detection and prompt treatment of in situ cancer and thus reduce breast cancer risk 30 .…”
Section: Discussionmentioning
confidence: 99%